RHEUMATIC MASKS OF PARANEOPLASTIC SYNDROME - A. P. Rebrov; I L Alexeyeva; E Y Kondiurina; V V Frontasieva; I F Shergina (Научно-практическая ревматология, 2001)
Summary Analysis of the prevalence and clinical manifestations of paraneoplastic syndrome in 173 patients with malignant tumors admitted in departments internal medicine of Regional Clinical hospital was done. Paraneoplastic syndromes was found in 13 patients (7%) and was characterized by the following rheumatic manifestations: articular syndrome, dermato- and polymyositis, lupus-like syndrome.